The use of beergame by students of an integrated technical course in administration (Research, Society and Development, 2021)
The application of information technology in the area of ​​education has always been a major factor in the area of ​​education, as it provides teachers with expanded teaching methods and students with more learning opportunities. This study aims to analyze the use of technology applied in the classroom, through the use of BeerGame, with third year students of the integrated technical course and relate them to the teaching and learning process, enabling a more attractive view in a way dynamics, facilitating the student's language and understanding. Therefore, this article considers that through the technological resources presented in the classroom, they can assist in learning, facilitating comprehension and placing the student in possible real everyday situations. Among the main observed benefits that the game can provide for teachers, we highlight the possibility of displaying and explaining various business concepts in addition to helping the integration of an abstract theoretical concept with practice; for the students, the fun of the game promotes learning and this experience becomes more effective. Another key point observed was the systematic understanding of complex concepts such as finance, economics, management, among others.